Fabrication of Ag–SnO2 Contact Materials from Gas‐Atomized Ag–Sn Powder Using Combined Oxidation and Ball‐Milling Process. Issue 2 (28th September 2015) - Choi, Sang‐Hoon; Ali, Basit; Kim, Song‐Yi; Hyun, Soong‐Keun; Seo, Suk‐Jun; Park, Kyoung‐Tae; Kim, Bum‐Sung; Kim, Taek‐Soo; Park, Jun Sung
Abstract : Silver–tin oxide (Ag–SnO2 ) is considered to be an effective alternative to silver–cadmium oxide (Ag–CdO), which is carcinogenic and, therefore, toxic to the human body. In this study, Ag–SnO2 powder was prepared through a combined oxidation and ball‐milling process using gas‐atomized Ag–Sn powder. During oxidation, the Ag3 Sn phase disappeared at 800°C and SnO2 was formed without Ag oxidation; this SnO2 formed a layer structure that covered the Ag matrix. The thickness of the oxide layer increased after the composite was subjected to a second oxidation process. Owing to the resultant core (Ag)‐shell (SnO2 ) structure, the electrical conductivity of the fabricated composite was considerably lower than that of commercially available materials. However, the electrical conductivity increased remarkably after ball milling of the samples, which allowed the SnO2 surface layer to be peeled off and crushed. Following high‐pressure magnetic pulsed compaction, the SnO2 was found to be homogeneously distributed in the Ag matrix, which exhibited a lamellar structure.